Pelatihan Aplikasi Komputer Bagi Staf dan Perangkat Desa Bahu Palawa Kecamatan Kahayan Tengah Kabupaten Pulang Pisau - Susi Hendartie; Muhammad Erfan; Bayu Pratama Nugroho; Hafiz Riyadli; Rommi Kaestria; Deden Andriawan (CV. Multi Kreasi Media, 2024)
Community Service conducted by STMIK Palangkaraya, especially by the faculty, is an activity from one of the Three Pillars of Higher Education that must be carried out at least once a year. The service activity carried out in Bahu Palawa Village, which is one of the villages in Kahayan Tengah Subdistrict, Pulang Pisau Regency, Central Kalimantan Province. The implemented service is community empowerment in the form of training focused on Microsoft Office, especially Microsoft Excel. This training was conducted to provide knowledge and skills for staff and village officials in processing data needed according to their respective job fields. The training was organized to help improve the abilities of the staff and village officials to perform tasks related to office administration. This activity has been carried out and has received a positive response from the staff and the community.